GAME-BASED LEARNING WITH MISSION CARDS IN ELEMENTARY SCHOOL - Maesarah; Maula Fatihal Ikhlas; Baiq Diana Safitri; Novi Sara Sagita; Haifaturrahmah (El Midad, 2025)
This study aims to enhance student learning activity by applying the Game-Based Learning model assisted by mission card media in Natural and Social Sciences. The research approach used is Classroom Action Research (CAR), carried out in two cycles, each consisting of three sessions. The research subjects were 33 third-grade students at SDN 2 Cakranegara. Data were obtained through observations of students' learning activities. The results showed an increase in the average student activity from 59.53% in Cycle I to 79.53% in Cycle II. These findings indicate that the Game-Based Learning model with mission card media is highly effective in improving student engagement in the learning process. This study affirms the importance of game-based learning innovations as an effective way to enhance activity and learning motivation in elementary education